Butylidenephthalide abrogates the myofibroblasts activation and mesenchymal transdifferentiation in oral submucous fibrosis. Issue 6 (17th April 2018) - Su, Tzu‐Rong; Liao, Yi‐Wen; Hsieh, Pei‐Ling; Tsai, Lo‐Lin; Fang, Chih‐Yuan; Lin, Taichen; Lee, Yu‐Hsien; Harn, Horng‐Jyh; Yu, Cheng‐Chia
Abstract: Oral submucous fibrosis (OSF) is a premalignant disorder in the oral cavity, and areca nut chewing habit has been implicated in the persistent activation of myofibroblasts and the subsequent fibrosis. Therefore, it is critical to ameliorate the excessive activities of myofibroblasts prior to the malignant transformation of OSF. In the current study, we evaluated the cytotoxicity of butylidenephthalide (BP), a major phthalide ingredient of Angelica sinensis, in fibrotic buccal mucosal fibroblasts (fBMFs) as well as various myofibroblast hallmarks, including the phenotypical characteristics and fibrosis‐related markers. Our results demonstrated that myofibroblast activities, including collagen gel contraction, migration, invasion and wound healing abilities were inhibited in response to BP. The expression levels of myofibroblast marker, α‐smooth muscle actin (α‐SMA), fibronectin and type 1 collagen A1 were decreased after exposure of BP. Moreover, we found that the EMT‐related markers, Twist, Snail and ZEB1 were all downregulated after BP treatment. Most importantly, our findings demonstrated that BP impeded the binding of Snail to the E‐box region in the α‐SMA promoter, which may lead to inhibition of the arecoline‐induced myofibroblast activities. Collectively, our data indicated that BP reduced numerous myofibroblast features in fBMFs and hindered the binding of Snail to α‐SMA, thereby may function as an effective and natural antifibrosis compound.